2012
DOI: 10.2527/jas.2011-4179
|View full text |Cite
|
Sign up to set email alerts
|

Transcript abundance of hormone receptors, mammalian target of rapamycin pathway-related kinases, insulin-like growth factor I, and milk proteins in porcine mammary tissue1

Abstract: Prolactin, glucocorticoids, and insulin are commonly used to induce milk protein synthesis in bovine mammary cell cultures. In addition, administration of GH increases milk yield in dairy cows, likely via the mammalian target of rapamycin (mTOR) pathway and IGF-I synthesis. As such, the hypothesis of this study was that mRNA abundance of hormone receptors, mammalian target of mTOR pathway-related kinases, IGF-I, and milk protein-encoding genes increases in the porcine mammary gland in response to greater lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Studies discussed above provide support for such an approach but the exclusive use of AA in this case is not enough and might be detrimental if there is not also a concomitant increase in energy in the diet in the form of carbohydrates [28]. Contrary to observations in the bovine, there is not significant increase in expression of insulin receptor and FRAP during lactation in the porcine mammary gland [171]; however, phosphorylation studies are not available in this species to provide conclusions about the activity of mTOR during lactation.…”
Section: How Insulin and Mtor Control Bovine Milk Protein Synthesis: mentioning
confidence: 89%
“…Studies discussed above provide support for such an approach but the exclusive use of AA in this case is not enough and might be detrimental if there is not also a concomitant increase in energy in the diet in the form of carbohydrates [28]. Contrary to observations in the bovine, there is not significant increase in expression of insulin receptor and FRAP during lactation in the porcine mammary gland [171]; however, phosphorylation studies are not available in this species to provide conclusions about the activity of mTOR during lactation.…”
Section: How Insulin and Mtor Control Bovine Milk Protein Synthesis: mentioning
confidence: 89%
“…This expression pattern for LAT1 is similar to the one reported previously by Aleman et al (3) in rats and Manjarin et al (20) in pigs and probably respond to the specific hormonal changes that occur during pregnancy and lactation. Recent studies have shown that Leu transamination and decarboxylation are stimulated by cortisol in rat mammary tissue and the glucocorticoid receptor NR3C1 curiously overlaps with the expression of the major milk proteins ␣-lactalbumin and ␤-casein in the porcine mammary gland (15,19). In contrast, the expression of the growth hormone receptor (growth hormone inhibits Leu transamination) tended to decreases with lactation.…”
Section: Discussionmentioning
confidence: 99%
“…As milk protein concentration is positively associated with dietary energy content (35) , the CLA-induced reduction in energy level may have reduced milk protein synthesis. In addition, trans-10, cis-12-CLA, but not the cis-9, trans-11 isomer, stimulates expression of the mammalian target of rapamycin in the mammary gland of the sows before initiating lactation, and it effects protein synthesis in this species (36,37) . As a mixture of these isomers was used, the milk protein reduction in the CLA-treated animals may be due to the isomer-specific action of cis-9, trans-11-CLA on mammalian target of rapamycin expression.…”
Section: Discussionmentioning
confidence: 99%